Genetic and phenotypic effects of chromosome segments introgressed from Gossypium barbadense into Gossypium hirsutum. - Weiwu Song; Mi Wang; Wei Su; Quanwei Lu; Xianghui Xiao; Juan Cai; Zhen Zhang; Shaoqi Li; Pengtao Li; Juwu Gong; Wankui Gong; Haihong Shang; et al. (PLoS ONE, 2017)
MBI9915 is an introgression cotton line with excellent fiber quality. It was obtained by advanced backcrossing and continuous inbreeding from an interspecific cross between the upland cotton (Gossypium hirsutum) cultivar CCRI36 as the recurrent parent and the sea island cotton (G. barbadense) cultivar Hai1, as the donor parent. To study the genetic effects of the introgressed chromosome segments in G. hirsutum, an F2 secondary segregating population of 1537 individuals was created by crossing MBI9915 and CCRI36, and an F2:3 population was created by randomly selecting 347 individuals from the F2 generation. Quantitative trait locus (QTL) mapping and interaction for fiber length and strength were identified using IciMapping software. The genotype analysis showed that the recovery rate for MBI9915 was 97.9%, with a total 6 heterozygous segments and 13 homozygous segments. A total of 18 QTLs for fiber quality and 6 QTLs for yield related traits were detected using the two segregating generations. These QTLs were distributed across 7 chromosomes and collectively explained 0.81%-9.51% of the observed phenotypic variations. Six QTLs were consistently detected in two generations and 6 QTLs were identified in previous studies. A total of 13 pairs of interaction for fiber length and 13 pairs of interaction for fiber strength were identified in two generations. Among them, 3 pairs of interaction for fiber length and 3 pairs of interaction for fiber strength could be identified in all generations; 4 pairs of interactions affected fiber length and fiber strength simultaneously. The results clearly showed that 5 chromosome segments (Seg-5-1, Seg-7-1, Seg-8-1, Seg-20-2 and Seg-20-3) have important effects on fiber yield and quality. This study provides the useful information for gene cloning and marker-assisted breeding for excellent fiber related quality.